(untitled) (Community Based Medical Journal, 2025)
Cerebrospinal fluid (CSF) rhinorrhea occurs due to abnormal leakage of CSF through the nasal cavity, often resulting from trauma, surgery, or spontaneous causes. Transnasal endoscopic repair has emerged as the preferred surgical approach due to its minimally invasive nature and high success rates. This prospective, observational study was conducted in four tertiary level specialized institutions in Dhaka, Bangladesh, between April 2023 and September 2024, to evaluate the outcomes of transnasal endoscopic repair of cerebrospinal fluid rhinorrhea. A total of 37 patients diagnosed with CSF rhinorrhea who underwent transnasal endoscopic repair were enrolled in this study through purposive sampling. Data was collected on patient clinical characteristics, site and size of the CSF leaks, surgical techniques, graft materials, and postoperative outcomes. Follow-up was conducted at regular intervals (2 weeks, 1, 3, 4 and 6 months) to assess the success or failure and monitor complications, if any. Trauma (45.90%), iatrogenic (10.80%), and spontaneous rhinorrhea (43.20%) were the main causes, with 49% of participants having chronic conditions. History of preoperative meningitis was present in 8.1% cases. Pre-operative anosmia was present in 27.03% cases. The cribriform plate was the most common leak site (43.2%), and smaller leaks (<1 cm²) were prevalent (67.6%). Encephalocele is present in 16.2% cases. Surgically, a combination of fascia lava, fat, and septal cartilage was most commonly used (56.8%), with the combined technique being the preferred approach (59.5%). Tissue glue was used in 54.1% cases. Merocel pack was used in 62.2% cases with a mean duration of pack was 5.59 days. Postoperatively, 45.9% received lumbar drains with an average duration of 5.47 days. A lumber drain was given to all the patients with spontaneous CSF rhinorrhoea and hypertensive patients. The average duration of hospital stay was 7.38 days. Post- operative complications like anosmia was present in 43.2% cases after 2 weeks, 24.3% cases after one month and was absent after 3 months, 4 months and 6 months. Complications like nasal oedema was present in 27.03% cases after 2 weeks, 16.23% cases after 1 month, 5.4% cases after 3 months and was absent after 4 months and 6 months. Synechia was present in 5.4% cases after 2 weeks, 2.7 % cases after 1 month and was absent after 3 months, 4 months and 6 months. Crusting was present in 89.19% cases after 2 weeks, 54.05% cases after one month, 2.7% cases after 3 months, 2.7% cases after 4 months and was absent after 6 months. The success rate for endoscopic repair was 89.2% after 6 months of follow-up. The combined surgical approach showed the best outcomes. Overall, while initial success rates were promising, the long-term outcomes highlighted areas for further investigation to reduce the risk of failures over time. CBMJ 2025 July: vol. 14 no. 02 P:57-65